The Limit of Structure Preservation in Dakota Lexical Phonology - Kyle, John (Kansas Working Papers in Linguistics, 1994)
Some of the earliest papers on Lexical Phonology claim that structure preservation applies throughout a Lexical derivation and may only he shut off by exiting the Lexicon. Work by Kellogg (1991) in Lakota attempts to uphold this relationship between Lexical Phonology and Structure Preservation but recent work in Lexical Phonology and some older work in Dakota refute this claim. After a minimal discussion of Dakota phonology, morphology and how they relate to each other in Lexical Phonology, I will take up the problem of syllable structure within the Lexicon and show that Structure Preservation seems to he shut off early in the Lexical derivation.